POST-COLONIAL THEORY: THE INTERSECTION OF TRADITION AND MODERNITY IN INDIAN POLITICS - Verma, Durgesh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In Indian politics, the meeting point of modernism and tradition exposes a complicated relationship moulded by the country's post-colonial legacy . Post-colonial theory offers a critical prism through which one could view how ideas, institutions, and political systems of India still show traces of colonial past. In the shifting political climate of India, modern ideas such as democracy, secularism, and economic liberalisation coexist with traditional values based in religion, caste, and regional identification. This study examines how these opposing forces interact, usually generating tensions and disparities in policymaking and government. Important questions illustrating the complexity of this junction include the function of caste in electoral politics, the influence of religious traditions on political ideologies, and the effect of economic reforms on the traditional rural economy. Moreover, the study looks at the Indian Constitution as a mix of modernism and legacy where provisions like the Uniform Civil Code and reservation policies denote continuous discussions. Case studies on gender politics, federalism, and environmental policy expose the ongoing need to strike a balance between history and the needs of a modern state. Furthermore discussed is how young people and digital media honour cultural legacy while developing current political identities. The paper concludes with evaluating the opportunities and difficulties India faces in negotiating twin currents of tradition and modernism in its political path, so implying that the future of Indian democracy will depend on how well it can coalesce several forces while managing newly emerging socio-political issues.